SUPPLIER RELATIONSHIP MANAGEMENT AS A TOOL FOR STRENGTHENING PARTNERSHIPS IN SUPPLY CHAIN - Branská, Lenka; Paták, Michal; Pecinová, Zuzana; Horák, Libor (STEF92 Technology Ltd., 2016)
If the company wants to reach the final, synergic effect in relation to their customers, it must also build relationships with its suppliers. They must become its partners. Therefore, it is necessary to build a relationship with them based on partnership. This requires a change in the company’s approach to its suppliers and the deployment of appropriate tools for the development of mutual relations. Therefore, the ways to manage relationships with suppliers and possibilities of development thereof became a subject of the primary qualitative research. The research was conducted in early 2016 in a company that is engaged in the production of nonwovens. The primary respondent was the head of the purchasing department. The aim was to find out how the company establishes relationships with its suppliers, how it evaluates and segments them and what tools it uses to develop the relationship and how. The results of the research were processed by content analysis. The research results show that the company segments its suppliers according to their importance and 38 of them are suppliers of the key segment. It cooperates with suppliers in several areas, especially in logistics, but also in research and development, quality management and financial management. The research has shown that the company assists its suppliers in improving their own service. Also, it is engaged in joint activities that improve the relationship, and initiatively helps in particular the key suppliers to solve their problems. This paper presents results of the primary research, evaluates them and suggests what joint activities may best contribute to improving the mutual relationship built on a partnership basis. The article contributes to the development of scientific knowledge in the area of Supplier Relationship Management and can also help managers in the corporate practice in the management of purchasing operations.
SUPPLIER RELATIONSHIP MANAGEMENT JAKO NÁSTROJ POSILOVÁNÍ PARTNERSTVÍ V ŘETĚZCI
Keywords: supplier; supplier relationship management; supply chain; supply chain management; customer value; Dodavatelsko-odběratelský řetězec; řízení vztahů s dodavateli; nástroje posilování vztahů